Halide Perovskite Nanocrystal‐Enabled Stabilization of Transition Metal Dichalcogenide Nanosheets. Issue 6 (19th December 2021) - Lee, Hyeokjung; Han, Hyowon; Park, Chanho; Oh, Jin Woo; Kim, Hong Hee; Kim, Sohee; Koo, Min; Choi, Won Kook; Park, Cheolmin
Abstract: Transition metal dichalcogenide (TMD) nanosheets exfoliated in the liquid phase are of significant interest owing to their potential for scalable and flexible photoelectronic applications. Although various dispersants such as surfactants, oligomers, and polymers are used to obtain highly exfoliated TMD nanosheets, most of them are electrically insulating and need to be removed; otherwise, the photoelectric properties of the TMD nanosheets degrade. Here, inorganic halide perovskite nanocrystals (NCs) of CsPbX3 (X = Cl, Br, or I) are presented as non‐destructive dispersants capable of dispersing TMD nanosheets in the liquid phase and enhancing the photodetection properties of the nanosheets, thus eliminating the need to remove the dispersant. MoSe2 nanosheets dispersed in the liquid phase are adsorbed with CsPbCl3 NCs. The CsPbCl3 nanocrystals on MoSe2 efficiently withdraw electrons from the nanosheets, and suppress the dark current of the MoSe2 nanosheets, leading to flexible near‐infrared MoSe2 photodetectors with a high ON/OFF photocurrent ratio and detectivity. Moreover, lanthanide ion‐doped CsPbCl3 NCs enhance the ON/OFF current ratio to >10 6 . Meanwhile, the dispersion stability of the MoSe2 nanosheets exfoliated with the perovskite NCs is sufficiently high. Abstract : Lanthanide ion‐doped inorganic halide perovskite nanocrystals are presented as non‐destructive dispersants capable of not only dispersing transition metal dichalcogenide nanosheets in the liquid phase but also enhancing the photodetection properties of the nanosheets, leading to a high performance near‐infrared image sensor.